Enhancer analysis of the Drosophila zinc finger transcription factor Earmuff by gene targeting - Kirsten Hildebrandt (BMC, 2021)
Abstract Background Many transcription factors are involved in the formation of the brain during the development of Drosophila melanogaster. The transcription factor Earmuff (Erm), a member of the forebrain embryonic zinc finger family (Fezf), is one of these important factors for brain development. One major function of Earmuff is the regulation of proliferation within type II neuroblast lineages in the brain; here, Earmuff is expressed in intermediate neural progenitor cells (INPs) and balances neuronal differentiation versus stem cell maintenance. Erm expression during development is regulated by several enhancers. Results In this work we show a functional analysis of erm and some of its enhancers. We generated a new erm mutant allele by gene targeting and reintegrated Gal4 to make an erm enhancer trap strain that could also be used on an erm mutant background. The deletion of three of the previously analysed enhancers showing the most prominent expression patterns of erm by gene targeting resulted in specific temporal and spatial defects in defined brain structures. These defects were already known but here could be assigned to specific enhancer regions. Conclusion This analysis is to our knowledge the first systematic analysis of several large enhancer deletions of a Drosophila gene by gene targeting and will enable deeper analysis of erm enhancer functions in the future.